Renewable energy in the Caribbean : report - James, Carlton A. (CARICOM Secretariat GeorgetownGY, 2009)
Presents the report following consultations with member states and main funding partners of CREDP to capture the commitment by Ministers of Energy to faciliate renewable energy initiatives, to document experiences, expertise, challenges and successes of energy initiatives at national and regional levels. Seeks to determine needs; identify resources and the capacity of the CARICOM Secretariat to respond to the role expected and stated by the stakeholders.